An evaluation of Shiraz University curriculum renewal process based on strategic approach of education for sustainable development. (3rd July 2019) - Mohammadi, Mehdi; Salimi, Ghasem; Ghasemian, Ana
This paper attempts to report key findings from some inquiries into the curriculum renewal process (CRP) which is hereby undergoing at Shiraz University. The research investigates into implementing sustainability criteria in the curriculum renewal process of the undergraduate programs based on a strategic approach to curriculum renewal. The existing gaps in the curriculum renewal process that can help pedagogues to embed sustainability throughout their programs are also being studied. The study is based on a sequential explanation of descriptive explanation. A survey is used to measure the gaps in curriculum renewal process at Shiraz based on the Dasha-Hargroves (2013) helix model. Also, fundamental reasons that cause the gaps are explored using in-depth, face to face and thematic analysis method. The results showed that there are some significant discrepancies between the curriculum renewal process under study and the rapid curriculum renewal model.